Role of ROS-mediated autophagy in radiation-induced bystander effect of hepatoma cells. (May 2015) - Wang, Xiangdong; Zhang, Jianghong; Fu, Jiamei; Wang, Juan; Ye, Shuang; Liu, Weili; Shao, Chunlin
Abstract Purpose: Autophagy plays a crucial role in cellular response to ionizing radiation, but it is unclear whether autophagy can modulate radiation-induced bystander effect (RIBE). Here, we investigated the relationship between bystander damage and autophagy in human hepatoma cells of HepG2. Materials and methods: HepG2 cells were treated with conditioned medium (CM) collected from 3 Gy γ-rays irradiated hepatoma HepG2 cells for 4, 12, or 24 h, followed by the measurement of micronuclei (MN), intracellular reactive oxygen species (ROS), mitochondrial membrane potential (MMP), and protein expressions of microtubule-associated protein 1 light chain 3 (LC3) and Beclin-1 in the bystander HepG2 cells. In some experiments, the bystander HepG2 cells were respectively transfected with LC3 small interfering RNA (siRNA), Beclin-1 siRNA or treated with 1% dimethyl sulfoxide (DMSO). Results: Additional MN and mitochondrial dysfunction coupled with ROS were induced in the bystander cells. The expressions of protein markers of autophagy, LC3-II/LC3-I and Beclin-1, increased in the bystander cells. The inductions of bystander MN and overexpressions of LC3 and Beclin-1 were significantly diminished by DMSO. However, when the bystander cells were transfected with LC3 siRNA or Beclin-1 siRNA, the yield of bystander MN was significantly enhanced. Conclusion: The elevated ROS have bi-functions in balancing the bystander effects. One is to cause MN and the other is to induce protective autophagy.